Il Cervino. Mediazioni di una Gestalt montana - Botta, Katia (Aesthetica Preprint, 2024)
The mountain presents itself as a particular case study through which to investigate the aesthetic category of the landscape and the related mediation processes. From the travel observations included by Horace-Bénédict de Saussure in his Voyages dans les Alpes up to 1865, the year the group led by the English alpinist Edward Whymper reached the summit, the pyramidal morphology of the Cervino (Matterhorn) has aroused the interest of travellers, naturalists but also reflections of an aesthetic, artistic and literary nature which find ample explanation in the multifaceted figure of the Englishman John Ruskin. Towards the middle of the XIX century, the form of the Matterhorn became a preferential object for contemporary pictorial representations, protagonists of a process of mediation partly still close to a contemplative approach (from an aesthetic-sensitive point of view) and mimetic (from an aesthetic-artistic point of view) but which, at the same time, anticipates that dimension of abstraction of the mountain corpus. Moreover, the Matterhorn, in the wake of Thomas George Bonney’s geological considerations and Guido Rey’s literary text, is not only the privileged object of mediating formulas of experience, but qualifies even earlier as a work of art of nature.